Canadian Journal of Law and Society (Cambridge)
The Canadian Journal of Law and Society (CJLS) is a bilingual periodical publishing innovative research in the broad field of law and society scholarship. Rooted in the distinctive Canadian Law and Society movement, CJLS features international scholarship concerning the intersection of law and sociology, cultural studies, literature, political science, criminology, history, human rights, gender studies and political economy.
Keywords: Law